An inappropriate defibrillator shock during ventricular tachycardia. - Faustino, M (2015)
Ventricular oversensing in patients with defibrillators is an infrequent but deleterious condition. We report a patient with a cardiac resynchronization-defibrillation device that presented with hyperkalemia and syncope. Device interrogation revealed ventricular double-counting within the QRS of a slow ventricular tachycardia, resulting detection of the slow ventricular tachycardia in the ventricular fibrillation zone, and delivery of an effective therapy, below device programmed detection rate. This case of defibrillator inappropriate detection emphasizes the relevance of device electrogram interrogation in order to minimize inappropriate therapies.